The prevalence of insomnia in university students and its relationship with quality of life: A university sample (Annals of Medical Research, 2022)
Aim: The goal of this study was to find out how common sleep disorders are among university students and to see how they relate to depression, anxiety, stress levels, personality factors, and overall quality of life.Materials and Methods: This study comprised a total of 856 students. Initially, Pittsburg Sleep Quality Index (PSQI) and a Sociodemographic Data Form were applied. Those with a PSQI score of ≥6 were scheduled for a second interview and a psychiatric interview was conducted. The participants were divided into two groups as those diagnosed with insomnia (n=104) and control group (n=95). Both groups were applied Insomnia Severity Index (ISI), Depression Anxiety Stress Scale (DASS), Eysenck Personality Questionnaire-Revised/Abbreviated Form (EPQR-S), and Short Form-36 (SF-36).  Results: Point prevalence of insomnia among study participants was 12.1%. Insomnia was more common in those who have just started university, were staying in dormitories, had a physical disorder, were smoking, had no regular breakfast habits, and were using electronic media more frequently. When compared to the control group, the ISI scores, DASS depression, anxiety, and stress scores, and EPQR-S neuroticism scores were statistically substantially higher in the insomnia group. Physical function, role limitation (physical), pain, general health, vitality (energy), social function, role limitation (emotional), and mental health were statistically substantially lower in the insomnia group than in the control group on the SF-36 subscales.Conclusion: Insomnia is a prevalent affliction among college students. In students with insomnia, depression and anxiety disorders are more common. Insomnia is also linked to a low quality of life and certain personality features.
Keywords: Insomnia; Depression; Anxiety; Personality; Quality of life